EFFECT OF VARIATION OF LUBRICANT CONCENTRATION (MAGNESIUM STEARATE) ON THE PHYSICAL QUALITY OF METOCLOPRAMID HCl TABLETS WITH DIRECT PRINTING METHOD - Puspadina, Valiandri; Budi Legowo, Deny; Fitriany, Erna; Priyoherianto, Andri; Damayanti, Winda (Indonesian Journal of Pharmaceutical Education, 2021)
Metoclopramide HCl is used to relieve nausea and vomiting. Market availability in the form of tablets, syrup and injection. The most preferred drug use by patients is oral medication because of its ease of use. Chewable tablets are a new product as an alternative for treatment in pediatric and adult patients who have difficulty swallowing drugs. This study aims to formulate the chewable tablet preparations of metoclopramide HCl using variations in lubricant concentrations. The variations of magnesium stearate with concentrations of 1%, 2%, and 3% using the direct printing method made to obtain a better physical quality test including organoleptics, weight uniformity, uniformity of size, tablet hardness, tablet brittleness, tablet crush time, uniformity of content. The results of the physical quality test were statistically analyzed using one way ANOVA to determine the effect of variations in the concentration of lubricants on the characteristics of chewable tablets. The results showed that variations in the concentration of magnesium stearate lubricant in the manufacture of metoclopramide HCl chewable tablets had an effect on the physical quality of metoclopramide HCl chewable tablets. The concentration of magnesium stearate which produces metoclopramide HCl chewable tablets with good physical properties is 2%.